2018
DOI: 10.1101/459453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Building a sequence map of the pig pan-genome from multiple de novo assemblies and Hi-C data

Abstract: 17Pigs (Sus scrofa) exhibit diverse phenotypes in different breeds shaped by the 18 combined effects of various local adaptation and artificial selection. To 19 comprehensively characterize the genetic diversity of pigs, we construct a pig pan-20 genome by comparing genome assemblies of 11 representative pig breeds with the 21 reference genome (Sscrofa11.1). Approximately 72.5 Mb non-redundant sequences 22 were identified as pan-sequences which were absent from the Sscrofa11.1. On 23 average, 41.7 kb of spurio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 52 publications
0
10
2
Order By: Relevance
“…Interestingly, in contrast to the observations in human, the repeat content of the newly assembled pan-sequences was similar to that of the reference pig genome assembly, and newly assembled repeats were more evenly distributed across categories [53]. This study also identified TIG3, an essential regulator of adipocyte lipolysis which displays presence/absence variation in pig populations, and could contribute to differences in physiology among pigs [53]. A previous study which analysed nine non-reference pig genomes reported 137 Mb of additional sequence harbouring 1,737 genes [54].…”
Section: Animal Pangenomescontrasting
confidence: 82%
See 3 more Smart Citations
“…Interestingly, in contrast to the observations in human, the repeat content of the newly assembled pan-sequences was similar to that of the reference pig genome assembly, and newly assembled repeats were more evenly distributed across categories [53]. This study also identified TIG3, an essential regulator of adipocyte lipolysis which displays presence/absence variation in pig populations, and could contribute to differences in physiology among pigs [53]. A previous study which analysed nine non-reference pig genomes reported 137 Mb of additional sequence harbouring 1,737 genes [54].…”
Section: Animal Pangenomescontrasting
confidence: 82%
“…The pangenome was constructed using 12 pig genomes, and 72.5 Mb of novel sequence was found, corresponding to ~3% of the genome. Interestingly, in contrast to the observations in human, the repeat content of the newly assembled pan-sequences was similar to that of the reference pig genome assembly, and newly assembled repeats were more evenly distributed across categories [53]. This study also identified TIG3, an essential regulator of adipocyte lipolysis which displays presence/absence variation in pig populations, and could contribute to differences in physiology among pigs [53].…”
Section: Animal Pangenomescontrasting
confidence: 52%
See 2 more Smart Citations
“…Additionally, QUOD is not restricted to plants, but could be applied to other species (e.g. pig [37]). However, an accurate determination of gene dispensability scores free of systematic biases might rely on a uniform selection of genomes from the respective taxonomic group and on uniform read coverage of genes.…”
Section: Discussionmentioning
confidence: 99%